Improving Basic Literacy Skills through the ‘Writing about Feelings’ Strategy in Class II.A Students at UPT SPF SDN Labuang Baji I - Rosa, Lediana; Hatimah, Husnul (Abjad Journal of Humanities & Education, 2024)
This research aims to improve the basic literacy skills of class II.A students at UPT SPF SDN Labuang Baji I through implementing the 'Writing About Feelings' strategy. This research is Classroom Action Research (PTK) which was carried out in two cycles, with each cycle consisting of planning, implementation, observation and reflection stages. The research subjects were 18 students in class II.A. Data collection techniques use observation, tests and documentation. Research instruments include observation sheets, basic literacy skills tests, and student writing portfolios. Data was analyzed descriptively qualitatively and quantitatively. The research results show an increase in students' basic literacy skills. In the initial conditions, only 40% of students achieved the minimum completeness criteria. After implementing the 'Writing About Feelings' strategy, in cycle I there was an increase to 60%, and in cycle II it reached 85%. This strategy has proven effective in increasing students' motivation and skills in reading and writing. Supporting factors include student enthusiasm and support from the school, while inhibiting factors include limited time and variations in students' initial abilities. In conclusion, the 'Writing About Feelings' strategy can improve the basic literacy skills of class II.A students at UPT SPF SDN Labuang Baji I. It is recommended that teachers can integrate this strategy in language learning and develop a variety of activities to accommodate diverse learning needs.